Patterns of Injuries and Illness Among Malaysian Contingents During the Kuala Lumpur South East Asia (KL SEA) Games 2017 - Salim, Ahmad Munawwar Helmi; Hamid, Mohamad Shariff A; Hussein, Kamarul Hashimy; Puji, Arshad (International Journal of Human and Health Sciences (IJHHS), 2021)
Introduction: Malaysia has participated in many international multi-sport events, but there is limited data on the injury and illness prevalence of the Malaysian contingent. Objective: The purpose of this study was to investigate the pattern of injuries and illnesses among the athletes and officials in the Malaysian contingent during the KL SEA Games 2017. Materials and methods: The medical records of the Malaysian contingent who received medical attention from the Malaysian medical team contingent during the centralised camp and the Games, were retrieved. The Malaysian medical team used a standardised injury and illness reporting form to record clinical and socio-demographic information of the athletes and officials in the Malaysian contingent. Results and Discussion: The total number of medical consultations received were 509 and 85.4% were with athletes. Two-hundred two injuries and 238 illnesses were diagnosed among the athletes. The most common injury among the athletes was muscle tears and strains, followed by ligamentous injuries, tendon injuries, bruises, and contusions. Majority of the injuries were mild and occurred during training. Recurrent injuries and increase in athlete’s age were significant predictors of injury severity. Comparable to earlier reports, the most common illness among athletes, was the respiratory system, followed by gastroenterology and dermatology. A total of 11 injuries and 58 illnesses were reported among the Malaysian contingent officials. Compared to athletes, the injury rate among the officials was much lower. The illness rate among the officials was half of the athletes’ illness rate, even though there was a higher prevalence of underlying chronic diseases among the officials. Conclusion: The rate of injuries and illness among Malaysian athletes in the KL Sea Games 2017 was comparable to previous reports. However, the rate of injuries and illness of the officials in the Malaysian contingent was lower compared to athletes. International Journal of Human and Health Sciences Vol. 05 No. 03 July’21 Page: 347-354